Post-hospitalization Daycare Treatment for Adolescents With Eating Disorders - Litmanovich-Cohen, Liron; Yaroslavsky, Amit; Halevy-Yosef, Liron Roni; Shilton, Tal; Enoch-Levy, Adi; Stein, Daniel (Frontiers in Psychiatry, 2021)
Background There are several possible facilities for the treatment of eating disorders (EDs). Specifically, there is the issue of the use of specialized daycare and ambulatory services over inpatient settings, and the place of daycare programs following inpatient treatment. Aim We sought to examine the contribution of post-hospitalization daycare program to the treatment of adolescents hospitalized with an ED. Methods: We assessed 61 female adolescents hospitalized with an ED. All but three were diagnosed with clinical or subthreshold anorexia nervosa (AN). Three were diagnosed with bulimia nervosa. Thirty-seven patients continued with a post-hospitalization daycare program for at least five months, whereas 24 did not enter, or were enrolled in the program for less than 5 months. Patients completed on admission to and discharge from inpatient treatment self-rating questionnaires assessing ED-related symptoms, body-related attitudes and behaviors, depression and anxiety. Social functioning was assessed 1-year from discharge using open-ended questions. One-year ED outcome was evaluated according to the patients' body mass index (BMI) and according to composite remission criteria, assessed with a standardized semi-structured interview. To be remitted from an ED, patients were required to maintain a stable weight, to have regular menstrual cycles, and not to engage in bingeing, purging and restricting behaviors for at least 8 consecutive weeks before their assessment. Results BMI was within normal range at follow-up, whether completing or not completing daycare treatment, and around 75% of the patients had menstrual cycles. By contrast, when using comprehensive composite remission criteria, less than a quarter of former inpatients not entering/not completing daycare program achieved remission, vs. almost a half of the completers. In addition, a greater percentage of completers continued with psychotherapy following discharge. Fifty percent of both groups showed good post-discharge social functioning. No between-group differences were found in the BMI and the scores of the self-rating questionnaires at admission to and discharge from inpatient treatment Conclusion Adolescent females with EDs can maintain a normal-range BMI from discharge to 1-year follow-up, even if not completing daycare treatment. By contrast, completion of a post-hospitalization daycare program may improve the 1-year follow-up ED-related outcome of former ED inpatients.